Orality in Writing: intercultural challenges in research with oralized cultures of West Africa - Angela Monteiro Pereira; Marisol Barenco de Mello; Miza Carvalho dos Santos (University of Bologna, 2024)
This article combines two studies that dialogue with the djeliw (Masters of the Word), transmitters of ancestral knowledge in the Manden people. Based on sensitive listening and African protagonism, the researches penetrated the ancestral memory of these societies, which define themselves based on their own rules and values. Oral documents, meetings with the djeli Kouyaté and the works of the philosopher Hampâté Bâ bring the two researches together. The studies revealed the performative character of the oral tradition, where knowledge is an act updated, recreated, revived at the moment it is practiced. This required the translation of this living perspective of knowledge and the nature of the oral word, maintaining qualities and values typical of the djeliw tradition not to make abstract knowledge that is the very life of a community. Considering that the methodological foundation is the dialogue between people, we seek the non-hierarchy of knowledge, to establish the same horizon of conversation in the intersection of voices. The aim is to build possible translations between orality and writing, to enrich debates in the field of intercultural education.